Running From Olympia to the Isles of the Blessed Sacrifice, Athleticism and Cosmology in a Panhellenic Hero Cult - Quinlan, Stephen (Université d'Ottawa | University of Ottawa, 2009)
This study explores the ritual features of the Pelops cult at Olympia from roughly the sixth century BCE to the second CE. It attempts to arrive at a sense of the meaningfulness of the sacrificial operations the cult contained, as revealed in the writings of Pindar and Pausanias. Of concern is how the ritual sacrifice, the blood offering, discloses a sense of mortal, embodied existence as it was experienced by the Greeks. Additionally, it seeks to explore the relationship between athletes and heroes within this context. The historical sources already noted are informed by means of comparative description with relevant material drawn from the poetry of Homer and Hesiod.